1996
DOI: 10.1002/(sici)1099-114x(199601)20:1<41::aid-er222>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

NOx emissions and thermal efficiencies of small scale biomass-fuelled combustion plant with reference to process industries in a developing country

Abstract: Solid biomass materials are an important industrial fuel in many developing countries and also show good potential for usage in Europe within a future mix of renewable energy resources. The sustainable use of wood fuels for combustion relies on operation of plant with acceptable thermal efficiency. There is a clear link between plant efficiency and environmental impacts due to air pollution and deforestation. To supplement a somewhat sparse literature on thermal efficiencies and nitrogen oxide emissions from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…However, it is a concern that combustion of biomass will lead to high levels of nitrogen oxides emissions (NO x ; collective term for NO and NO 2 ) from oxidation of nitrogen in the fuel (fuel nitrogen) or potentially conversion of nitrogen in the air (air nitrogen). NO x are contributing to environmental problems such as acid rain, photochemical smog formation and depletion of stratospheric ozone [2]. Also nitrous oxide (N 2 O) may be formed, having a strong greenhouse gas effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is a concern that combustion of biomass will lead to high levels of nitrogen oxides emissions (NO x ; collective term for NO and NO 2 ) from oxidation of nitrogen in the fuel (fuel nitrogen) or potentially conversion of nitrogen in the air (air nitrogen). NO x are contributing to environmental problems such as acid rain, photochemical smog formation and depletion of stratospheric ozone [2]. Also nitrous oxide (N 2 O) may be formed, having a strong greenhouse gas effect.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental studies have shown that these three mechanisms are contributing much less to NO x formation in biomass combustion than fuel-N conversion. Regarding the first route, this is because the Zeldovich mechanism is predominant at temperatures greater than 1500°C [2,3], while the temperatures during biomass combustion for power production are typically lower. Contributions from the prompt mechanism are mainly found for fuel rich and high temperature conditions which are also not relevant in biomass combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Discussions are underway, however, to amend this time limitation and to extend authorization to a three-year period. Although the National Environmental Act is the major item of legislation concerning industrial pollution, government environmental priorities are outlined in the National Environmental Action Plan 1992-1996(Government of Sri Lanka, 1991. This is an ambitious programme to address a whole range of environmental concerns.…”
Section: Review Of Environmental Legislation In Sri Lankamentioning
confidence: 99%
“…Under the Climate Change Agreement, Sri Lanka has agreed to reduce greenhouse gas emissions to 1990 levels by the year 2000, although the actual level of emissions in 1990 is unknown. The data in this paper provides part of the information required, and the procedures developed (Tariq and Purvis, 1996) can be used to estimate total national emissions from the national energy consumption data. In the case of the Montreal protocol, Sri Lanka has agreed to phase out the use of CFCs by the year 2000 -except for the maintenance of existing units.…”
Section: Review Of Environmental Legislation In Sri Lankamentioning
confidence: 99%
See 1 more Smart Citation